2023
DOI: 10.4047/jap.2023.15.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial aging on mechanical and physical properties of CAD-CAM PMMA resins for occlusal splints

Júlia Correa Raffaini,
Eduardo Jose Soares,
Rebeca Franco de Lima Oliveira
et al.

Abstract: PURPOSE This study aimed to assess and compare the color stability, flexural strength (FS), and surface roughness of occlusal splints fabricated from heat-cured acrylic resin, milled polymethyl methacrylate (PMMA)-based resin, and 3D-printed (PMMA) based-resin. MATERIALS AND METHODS Samples of each type of resin were obtained, and baseline measurements of color and surface roughness were recorded. The specimens were divided into three groups (n = 10) and subjected to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This finding is confirmed by the results of a study by Revilla Leon et al [ 49 ]. In general, there are several studies indicating an overall negative affect of aging on printable resins [ 14 , 18 , 37 , 39 , 53 , 54 ], and also one recent study that indicates that although there are negative effects on the mechanical properties, those are not significant [ 36 ]. Some other studies have proven the negative effect of aging on other 3D-printed objects, like complete denture bases and models [ 39 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is confirmed by the results of a study by Revilla Leon et al [ 49 ]. In general, there are several studies indicating an overall negative affect of aging on printable resins [ 14 , 18 , 37 , 39 , 53 , 54 ], and also one recent study that indicates that although there are negative effects on the mechanical properties, those are not significant [ 36 ]. Some other studies have proven the negative effect of aging on other 3D-printed objects, like complete denture bases and models [ 39 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lutz described a volume loss of AM splints after artificial aging [ 18 ]. In addition, it has been shown that AM splints have a lower surface roughness after aging than SM [ 36 ]. However, a negative effect of artificial aging on mechanical properties of AM splints materials has also been described [ 26 , 37 ].…”
Section: Introductionmentioning
confidence: 99%